2012
DOI: 10.1111/j.1365-2141.2012.09209.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of diffuse large B‐cell lymphoma presenting in leukaemic phase

Abstract: Summary Diffuse large B‐cell lymphoma (DLBCL) occasionally presents with circulating malignant cells. The clinical characteristics and long‐term outcomes of these patients have not been described. Twenty‐nine newly diagnosed DLBCL presenting in leukaemic phase were identified between 1996 and 2010, at two institutions. Median age was 48 years, and patients presented with leucocytosis, high lactate dehydrogenase levels, B symptoms, and high International Prognostic Index score. Extra nodal site involvement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 28 publications
4
40
1
Order By: Relevance
“…Based on this data, patients with FL-LP at diagnosis should be considered as having a more aggressive disease course, relative to other indolent NHL. The same finding was also reported in DLBCL, where the prognostic value of LP has been recently associated with a worse outcome (Berger et al, 2000;Nodit et al, 2003;Rubio-Moscardo et al, 2005;Ondrejka et al, 2011;Muringampurath-John et al, 2012;Nygren et al, 2012). Although approximately one-third of the patients included in this series experienced long term TTP, all patients should be monitored carefully during and after first-line treatment to consider more intensive treatment, such as ASCT, when feasible as a therapeutic option to achieve a sustained response, especially if a complete response is not achieved or if their disease progresses shortly after their initial therapy.…”
Section: Discussionsupporting
confidence: 78%
“…Based on this data, patients with FL-LP at diagnosis should be considered as having a more aggressive disease course, relative to other indolent NHL. The same finding was also reported in DLBCL, where the prognostic value of LP has been recently associated with a worse outcome (Berger et al, 2000;Nodit et al, 2003;Rubio-Moscardo et al, 2005;Ondrejka et al, 2011;Muringampurath-John et al, 2012;Nygren et al, 2012). Although approximately one-third of the patients included in this series experienced long term TTP, all patients should be monitored carefully during and after first-line treatment to consider more intensive treatment, such as ASCT, when feasible as a therapeutic option to achieve a sustained response, especially if a complete response is not achieved or if their disease progresses shortly after their initial therapy.…”
Section: Discussionsupporting
confidence: 78%
“…From 1996 to 2010, only 29 cases of leukemic DLBCL were diagnosed at UNMC and Emory University School of Medicine. 5 The unusual presentation of lymphoma masquerad-ing as leukemia and the rarity of the association between myeloproliferative disorders and lymphoma can potentially result in a misdiagnosis of acute leukemia. Therefore, a high index of suspicion and a thorough bone marrow biopsy evaluation using immunohistochemistry, flow cytometry, and cytogenetic studies and traditional morphological assessment are important for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In one study DLBCL masquerading as leukemia was associated with a high tumor burden, frequent extranodal involvement, complex bone marrow cytogenetics, and a high rate of complications and death during induction, but was associated with an approximately 50% 4-year survival rate in patients able to tolerate anthracycline and rituximab-based regimens. 5…”
Section: Discussionmentioning
confidence: 99%
“…Tumor‐specific DNA fragments can be detected noninvasively in the blood in both cellular (circulating tumor cells [CTCs]) and cell‐free (circulating‐tumor DNA [ctDNA]) forms (Figure ). In certain lymphomas such as DLBCL, however, CTCs are rare with recent data indicating a possible relationship between defective homing pathways and systemic dissemination . Multiple studies have demonstrated higher levels of cell‐free circulating DNA (cfDNA) in cancer patients compared with healthy controls from the constant shedding of DNA fragments into the peripheral blood from cancer cells undergoing apoptosis, secretion, and necrosis.…”
Section: Advances In Molecular Monitoring Methods For Nhlmentioning
confidence: 99%